Evaluation of autonomic function underlying slow postexercise heart rate recovery - Davrath, L. R.; Akselrod, S.; Pinhas, I.; Toledo, E.; Beck, A.; Elian, D.; Scheinowitz, M. (Medicine & Science in Sports & Exercise, 2006)
The reduction in heart rate (HR) during the first minute of recovery immediately after a graded maximal exercise stress test (GXT) has recently been found to be a powerful and independent predictor of cardiovascular and all-cause mortality. Reduced vagal activity has been postulated as the cause, but this has not been proven in a population with slow HR recovery (HRR).